Information technology and communication in nursing education - C. R. B. Costa; H. Cassiolato; K. M. Alonso (Scientific Electronic Archives, 2014)
The use of information and communication technologies in education, transforms not only the way we communicate, but also work, decide and think, as well as allows you to create rich, complex and diversified learning situations, through sharing the tasks between teachers and students , providing an interactive, continuous and lifelong learning. The paper aims to reflect on the importance of the use of information and communication technologies in higher education and show the potential in promoting changes and challenges for teachers of undergraduate nursing course. This is a literary review concerning the issue at hand, in the period from February to March 2014. The result indicates that the resources of information and communication technologies are strategies for the education of future nurses and promote the changing process for teachers , providing quality education to students and understanding that we must seek new opportunities to build a new style of training.